THE TRANSFORMATION OF FAIRY TALE TRADITIONS IN MODERN AMERICAN FICTION - Lola Jalilova Jalilovna; Ro‘zigul Olimova (Bright Mind Publishing, 2026)
Fairy tales have traditionally functioned as symbolic narratives rooted in magic, fantasy, and moral absolutism. In contemporary American literature, however, these narratives undergo significant transformation, reflecting modern social realities, psychological depth, and cultural complexity. This article aims to examine how contemporary American writers reinterpret and transform classical fairy tale motifs, structures, and archetypes, shifting them from magical frameworks to realistic, often critical representations of modern life. The study employs a qualitative literary analysis based on close reading and comparative methods. Selected contemporary American literary texts are analyzed in relation to their classical fairy tale sources, with particular attention to narrative structure, character transformation, and thematic reorientation. The analysis reveals that contemporary adaptations frequently replace magical elements with realistic or psychological explanations, reinterpret archetypal characters as morally ambiguous figures, and use fairy tale frameworks to address issues such as identity, gender, trauma, and social injustice. This transformation reflects a broader postmodern tendency toward deconstruction and intertextuality. The metamorphosis of fairy tales in contemporary American literature demonstrates the genre’s adaptability and continued relevance. By moving from magic to reality, modern authors preserve the cultural memory of fairy tales while reshaping them to engage critically with contemporary human experience.
Keywords: Fairy tale transformation, contemporary American literature, reinterpretation, realism, postmodernism, intertextuality, narrative adaptation, cultural symbolism.